2015
DOI: 10.1136/bmjopen-2014-006804
|View full text |Cite
|
Sign up to set email alerts
|

Perception and use of massive open online courses among medical students in a developing country: multicentre cross-sectional study

Abstract: ObjectivesTo assess the prevalence of awareness and use of massive open online courses (MOOCs) among medical undergraduates in Egypt as a developing country, as well as identifying the limitations and satisfaction of using these courses.DesignA multicentre, cross-sectional study using a web-based, pilot-tested and self-administered questionnaire.SettingsTen out of 19 randomly selected medical schools in Egypt.Participants2700 undergraduate medical students were randomly selected, with an equal allocation of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 14 publications
2
44
2
Order By: Relevance
“…This agrees with the findings of Ecclestone (2013) a less moderate level of satisfaction but less satisfaction with student-instructor and studentstudent interaction (Aboshady et al, 2015).…”
Section: Participation In Moocsupporting
confidence: 82%
See 2 more Smart Citations
“…This agrees with the findings of Ecclestone (2013) a less moderate level of satisfaction but less satisfaction with student-instructor and studentstudent interaction (Aboshady et al, 2015).…”
Section: Participation In Moocsupporting
confidence: 82%
“…Students can follow the course content at their own pace, lectures can be replayed for a better understanding of concepts, participants can interact with many others from around the world, and student's learning outcome is assessed through well-designed online quizzes and assessment tools (Aboshady et al, 2015;Ecclestone, 2013). Advocates of MOOCs consider them a means of providing quality education through the virtual classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Aboshady et al (2015) found a high awareness of MOOCs in a survey of Egyptian medical students: 30% had enrolled in at least one MOOC. Research on MOOCs in developing country contexts is, however, sparse (Castillo, Lee, Zahra & Wagner, 2015) and mostly limited to participation of developing country users in western MOOCs (Garrido et al, 2016;Christensen et al, 2013;Ho et al, 2015), where there tends to be low participation from Asia and especially Africa (Liyanagunawardena, Williams & Adams, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The MOOC participants also stated that subtitles in English were helpful. Contrarily, for example, Aboshady et al [17] did not find English as a significant barrier in their investigation of Egyptian medical students' perspective towards a MOOC delivered in English (less than 20% of the students struggled). It may be due to medical students' advanced level of education.…”
Section: Introductionmentioning
confidence: 99%